2022
DOI: 10.3390/ma15062045
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Acid Concentration, Time and Using a Two-Part Silane Potentiates Bond Strength of Lithium Disilicate–Reinforced Glass Ceramic to Resin Composite: An Exploratory Laboratory Study

Abstract: There is still a lack of consensus concerning the recommended etching concentration, application time and type of silane when bonding lithium disilicate-reinforced glass ceramics manufactured by CAD/CAM. The purpose of this study was thus to conduct an in vitro study which investigates the influence of hydrofluoric acid (HF) concentration, etching time and silane type on the microtensile bond strength (μTBS) of lithium disilicate to resin composites. Thirty-nine IPS e.max CAD blocks were randomly divided betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…It was observed that with the increase in of the crystallization rate of CAD/CAM dental restoration materials, the solubility level decreased [ 40 ]. Additionally, there were substantial differences in the proportion of chemical components among the products from diverse manufacturers, which led to various etching-time procedures [ 41 ]. The recommended conditioning practice comprised etching with 5% to 10% hydrofluoric acid (HF), with etching time varying from 15 s to 90 s [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was observed that with the increase in of the crystallization rate of CAD/CAM dental restoration materials, the solubility level decreased [ 40 ]. Additionally, there were substantial differences in the proportion of chemical components among the products from diverse manufacturers, which led to various etching-time procedures [ 41 ]. The recommended conditioning practice comprised etching with 5% to 10% hydrofluoric acid (HF), with etching time varying from 15 s to 90 s [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors were also concerned that over-etching the ceramic might reduce the strength of the material [ 46 ]. Other studies have also raised the aspect of the weakening effect that HF acid produces, regardless of the action time or concentration [ 41 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 localizes the resin-ceramic interfaces of interest for a schematic bonding system in dental restoration when the ceramic surface is prepared by hydrofl uoric acid (HF-etching) followed by a silane treatment and fi nished with the adhesive resin cement layer. In the literature, it is well known that ceramic surface pre-treatment helps to improve the bonding properties at the resin-ceramic interface [1][2][3][4][5][6][7][8][9][10][11]. Silanes are hybrid functional monomers able to form chemical bonds with organic and inorganic surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…chemical bonding). The stability and effectiveness of this adhesion are also supposed to be improved by heat treatment [11][12][13][14][15][16][17]. Bruzi, et al [16] based on the evaluation of the shear bond strength of composite resin to CAD/CAM lithium disilicate ceramics recommends a regular application of silane.…”
Section: Introductionmentioning
confidence: 99%